2021
DOI: 10.1038/s41467-021-22269-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictive biomarkers of Clostridioides difficile infection in hospitalized patients receiving broad-spectrum antibiotics

Abstract: Trial enrichment using gut microbiota derived biomarkers by high-risk individuals can improve the feasibility of randomized controlled trials for prevention of Clostridioides difficile infection (CDI). Here, we report in a prospective observational cohort study the incidence of CDI and assess potential clinical characteristics and biomarkers to predict CDI in 1,007 patients ≥ 50 years receiving newly initiated antibiotic treatment with penicillins plus a beta-lactamase inhibitor, 3rd/4th generation cephalospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
1
23
2
Order By: Relevance
“…In some cases, antibiotics even promote CDIs, which can take over after the symbiotic microflora is damaged by antibiotics ( Theriot et al, 2014 ). These broad-spectrum antibiotics affect the healthy gut microbiota and hinder colonization resistance by reducing the abundance of intestinal microbes that resist C. difficile ( van Werkhoven et al, 2021 ). In turn, the reduced microbiota diversity induces an elevated level of primary bile acids (BAs), which facilitate the germination of C. difficile spores and reduce the concentration of secondary BAs that inhibit the growth of C. difficile ( de Aguiar Vallim et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, antibiotics even promote CDIs, which can take over after the symbiotic microflora is damaged by antibiotics ( Theriot et al, 2014 ). These broad-spectrum antibiotics affect the healthy gut microbiota and hinder colonization resistance by reducing the abundance of intestinal microbes that resist C. difficile ( van Werkhoven et al, 2021 ). In turn, the reduced microbiota diversity induces an elevated level of primary bile acids (BAs), which facilitate the germination of C. difficile spores and reduce the concentration of secondary BAs that inhibit the growth of C. difficile ( de Aguiar Vallim et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many publications on C. difficile [23][24][25][26][27][28][29][30][31][32][33][34][35] have been published, but the vast majority of them presented general information about the microorganisms, the number of diagnosed cases, methods of diagnosis, patient treatment and transmission routes. Definitely much fewer papers discuss the issues related to the knowledge of healthcare professionals about C. difficile, seniority, the etiology of CDI in medical facilities, costs of treating patients with nosocomial infections and the responsibility of hospital management for training and supervising subordinate medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Werkhoven and collaborators (2021) showed that the carriage of toxigenic C. difficile increased the incidence of developing CDI 10-fold after antibiotic treatment. Specifically, the use of carbapenem increased the incidence of CDI 5-fold and increased the abundance of Enterococcus 5-fold [ 13 ].…”
Section: Microbiota Associated With Asymptomatic Colonization and CDImentioning
confidence: 99%
“…Antibiotic exposure increases the possibility of C. difficile colonization by 3.7-fold [ 12 ] and of developing CDI by 3.55-fold [ 9 ]. A previous study showed that among antibiotic-associated diarrhea (AAD) cases, the incidence of CDI was 1.14–1.89% [ 13 ], and the frequency of toxigenic C. difficile carriage was 18.1–19.0% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%